PERAN PEMERINTAH TERHADAP PENGEMBANGAN INDUSTRI KREATIF SEKTOR PARIWISATA (STUDI KASUS : KABUPATEN ACEH TENGAH) - Muliadi Muliadi; Putri Bintusy Syathi (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractCentral Aceh has a large tourism potential but has not been utilized optimally. Therefore, thisstudy aims to examine the role of government in encouraging the development of creativeindustry tourism sector in central Aceh district. The data used in this research is the primarydata obtained through a live interview using a questionnaire. Total samples in this study as muchas 11 crafts souvenir business units. The results showed that the government has made severalefforts such as providing assistance, ease in business license management, provide professionalbusiness mentor, provide mentoring and also provide promotional facilities through the mediaElectronic and print media. Nevertheless, the confirmation from the entrepreneur is notappropriate. Therefore, there needs to be socialization from the government for creative industryentrepreneurs to make the results more maximal.Keywords: Tourism, Creative Industries, Government Policy.